Velg material strength Analysis Of Cast Motorcycle Wheel and Spoke Wheel Of Testing Impact - Albakhori M R (International Conference on Engineering and Technology Development (ICETD), 2017)
The use of motorcycles, power wheels is important, because the wheels is one part of the vehicle that receives the voltage and load is quite high. The road surface may result in stress and deformation in the casting wheel andspokewheel.Coupled with the speed of the riders who willinfluence the price impact of the cast wheel and spokewheel.Rims types of cast wheel and spoke wheel take the road within 0 hours, 2 hours, 4 hours. Having both types of motorcycle wheels are brought walked, then will be cutting the specimen in order to do impact testing. Testing here will know the impact of energy produced from these two types of alloy wheels. Each specimen specimens will be tested the impact will have a different impact prices, as influenced by the temperature at the spinning wheel and will affect the temperature of the wheels are mounted on the motorcycle used. Impact test results obtained from the difference in price impact of both types of wheels under the influence of the length of time running from the second wheel.